Physical–biological interactions influencing large toothfish over the Ross Sea shelf. Issue 6 (7th September 2017) - Ashford, Julian; Dinniman, Michael; Brooks, Cassandra
Abstract: We add comments to a recent series of publications in peer-reviewed journals concerning the distribution of large Antarctic toothfish ( Dissostichus mawsoni ) found over the inner shelf of the Ross Sea. We note that earlier fish ecologists advanced innovative hypotheses invoking physical–biological interactions with life history, and that these, far from being disproved, have been relegated by more immediately pressing management concerns. We argue that, despite the considerable advances achieved by research groups working on D. mawsoni, an understanding of distribution and abundance is incomplete without reference to the physical structure that supports their life history. We briefly consider hypotheses highlighted by the recent literature in the context of major features of the shelf circulation in the Ross Sea, in particular intrusions of modified Circumpolar Deep Water along trough systems. We suggest physical–biological interactions that may be involved and call for improvements in the monitoring programme that can help test between the competing hypotheses.